An Experimental Study on Freezing of Kulfi using Cryogen - Barge, Rahul S; Barnwal, Pradyuman; Deep, Ankit; Wale, Gaurav S (Indian Journal of Dairy Science, 2018)
In this communication, an experimental study on freezing of kulfi using cryogen (liquid nitrogen) has been presented. For this investigation, an experimental set up (insulated cylindrical vessel) was fabricated for freezing of kulfi using cryogen (liquid nitrogen). The characteristics of kulfi, e.g. melting rate and sensory attributes, were compared for both cryogenic and conventional methods of freezing. Kulfi is an indigenous frozen milk product, popular in northern region of India. Traditionally, kulfi is made by concentrating whole milk to about two folds followed by addition of sugar and freezing it in aluminium or plastic moulds (usually of conical shape). Rapid freezing gives small ice crystal formation even uniformly distributed in product matrix as compared to slow freezing. Based on preliminary trials for cryogenic and conventional freezing of kulfi, freezing time of 160 s, 180 s, 200 s, 220 s and 240 s were selected for cryogenic (liquid nitrogen) and that of 105 min, 120 min, 135 min, and 150 min were selected for conventional (ice-salt mixture) freezing of kulfi. The melting rates of kulfi, prepared by cryogenic method, for freezing time of 160 s, 180 s, 200 s, 220 s and 240 s were 0.67±0.01 ml/min, 0.66±0.10 ml/min, 0.66±0.03 ml/min, 0.68±0.01 ml/min and 0.67±0.04 ml/min, respectively. The melting rates for kulfi samples for freezing time of 105 min, 120 min, 135 min, and 150 min were 0.96±0.05 ml/min, 0.83±0.04 ml/min, 0.93±0.002 ml/min, 0.78±0.03 ml/min, respectively. Melting rates of the kulfi, prepared by cryogenic method, had lower values than that of the conventional method. Kulfi obtained with freezing time of 220 s (for 50 g kulfi) by cryogenic method and that of 120 min by conventional method were observed the highest sensory scores. Kulfi prepared with cryogenic method scored higher sensory values than that of the conventional method. The liquid nitrogen required to freeze one kg of kulfi is 2.06 kg when the exhaust gaseous form of liquid nitrogen was at a temperature of -145°C. The liquid nitrogen requirement may reduce further by harnessing the cooling potential of the exhaust gaseous form of liquid nitrogen from -145°C to lower values by pre-cooling or pre-freezing of the kulfi moulds.